La vegetation du Paraguay - Resultats Scientifiques d'une Mission Botanique Suisse au Paraguay - Vischer, W. (1916)
Flora Paraguay
Keywords: Flora; Anatomia; Paraguay; Plantas Acuaticas; Plantas Parasitas; Lianas